(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Mechanical and physical properties are potentially very important for biomaterials to be used as scaffolds. To investigate the effect of adding keratin to polylactic acid (PLLA) on the mechanical and physical properties of electrospun nonwoven fibrous membranes, a series of experiments were conducted, with PLLA/keratin mass proportions of 1:0, 2:1, 1:1, 1:2, 1:4 and 1:8 respectively. Measured mechanical and physical properties include tensile property, compressional property, water vapor permeability, moisture content and moisture management property. The results show that with an increase in the keratin content, tensile property of above membranes decreased; while moisture content and hydrophilicity are increased; compressional property and water vapor permeability, however, are not influenced significantly. It could be concluded from the experimental results that adding keratin into PLLA would significantly change some important mechanical and physical properties of electrospun nonwoven fibrous membranes, which could influence their performances as scaffolds for tissue engineering.